2018
DOI: 10.1038/s41467-018-04620-y
|View full text |Cite
|
Sign up to set email alerts
|

SKP2- and OTUD1-regulated non-proteolytic ubiquitination of YAP promotes YAP nuclear localization and activity

Abstract: Dysregulation of YAP localization and activity is associated with pathological conditions such as cancer. Although activation of the Hippo phosphorylation cascade is known to cause cytoplasmic retention and inactivation of YAP, emerging evidence suggests that YAP can be regulated in a Hippo-independent manner. Here, we report that YAP is subject to non-proteolytic, K63-linked polyubiquitination by the SCFSKP2 E3 ligase complex (SKP2), which is reversed by the deubiquitinase OTUD1. The non-proteolytic ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 53 publications
4
100
0
Order By: Relevance
“…Together with these studies, our current work further demonstrates a complicated machinery for fine and tight control of YAP activity under various cellular contexts. Interestingly, some negative regulators of YAP, such as MST4 kinase characterized here, and the reported SET1A (Fang et al, 2018), RUNX3 (Qiao et al, 2016), and OTUD1 (Yao et al, 2018), were found to be down-regulated in different cancer specimens and to be associated with poor prognosis. Perhaps dysregulation of these YAP-related tumor suppressors could explain the hyperactivation of YAP in cancer cells without apparent change of the classic Hippo kinase cascade.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Together with these studies, our current work further demonstrates a complicated machinery for fine and tight control of YAP activity under various cellular contexts. Interestingly, some negative regulators of YAP, such as MST4 kinase characterized here, and the reported SET1A (Fang et al, 2018), RUNX3 (Qiao et al, 2016), and OTUD1 (Yao et al, 2018), were found to be down-regulated in different cancer specimens and to be associated with poor prognosis. Perhaps dysregulation of these YAP-related tumor suppressors could explain the hyperactivation of YAP in cancer cells without apparent change of the classic Hippo kinase cascade.…”
Section: Discussionmentioning
confidence: 53%
“…The Hippo–YAP pathway can respond to a wide range of stress signals, eventually leading to the manifestation of different states of YAP-dependent gene transcription. Recently, a burst of studies have identified various types of PTMs including ubiquitination, methylation, and O-GlcNAcylation to regulate YAP activation in Hippo-independent manners (Fang et al, 2018; Peng et al, 2017; Yao et al, 2018; Zhang et al, 2017, 2019). Together with these studies, our current work further demonstrates a complicated machinery for fine and tight control of YAP activity under various cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings of a different study, which reported that the ectopic expression of CSIG did not influence p16 INK4a expression and that CSIG negatively regulated p27 Kip1 expression to promote cell proliferation by inhibiting PTEN translation 21 . Skp2 may stabilize CSIG through nonproteolytic polyubiquitination, as demonstrated by its regulation of yes-associated protein and liver kinase B1 22,23 , and thereby promote p27 Kip1 degradation. Although p53 expression was also induced by Skp2 ectopic expression, its level actually was decreased in replication-induced old EPCs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4b). 327 The Wnt signaling pathway, associated with CSC stemness maintenance, also plays an important role in regulating the stability and degradation of TAZ. Phosphorylated β-catenin can serve as a platform for TAZ and β-TrCP1 and promotes TAZ degradation by β-TrCP1.…”
Section: Nanog Ubiquitinationmentioning
confidence: 99%